Influence of interfacial friction and specimen configuration in Split Hopkinson Pressure Bar system. (October 2015) - Zhong, W.Z.; Rusinek, A.; Jankowiak, T.; Abed, F.; Bernier, R.; Sutter, G.
Abstract: Influences of interface friction and specimen configuration on the material dynamic response using split Hopkinson pressure bar (SHPB) experiment are evaluated using nonlinear finite element (FE) analysis. The effect of various friction conditions between specimen and the transmitted/incident bars in SHPB system is investigated for different specimen geometries. Cylindrical and cuboid specimens with one- and four-layered configurations are adopted and the stress states along the specimen are analyzed. Results indicate that the transmitted signal decreases and the reflected signal increases with friction coefficient increasing. Interface friction brings great variation in stress triaxiality and Lode parameters in the SHPB specimen. Experimental tests are also conducted in this study to verify the conclusions made through FE simulations. Highlights: Interface friction brings stress triaxiality and Lode parameter in SHPB. Interface friction induces inaccurate strain rate and flow stress values in SHPB. Cylinder layered SHPB specimen is an option to be used for thin plate material. Stress wave convergence of cuboid sheet has been investigated in SHPB experiment. A significant effect on uniaxial and uniformity stress assumptions was noticed.